Intestinal obstruction due to idiopathic mesenteric phlebosclerosis colitis: A case report - Shan, Jiaqi; Chen, Fangci; Yu, Panpan (Frontiers in Surgery, 2022)
Abstract Introduction: Idiopathic mesenteric phlebosclerosis colitis (IMP) is a rare condition that impairs colonic venous blood return owing to mesenteric venous sclerosis and fibrosis. At present, many studies have suggested that long-term intake of Chinese herbal medicines is associated with its pathogenesis. IMP has no characteristic clinical manifestations, and most patients with IMP present with acute intestinal obstruction. As a rare disease, the etiology, pathogenesis, pathophysiology, and treatment of IMP are being explored and studied. Case Description: A 60-year-old male patient with IMP was admitted to our hospital for acute intestinal obstruction, received subtotal colectomy and ileostomy after 10 days of ineffective conservative treatment, and was discharged after postoperative supportive treatment for 1 month. Discussion: The most common complication in patients with IMP is intestinal obstruction, followed by bleeding and intestinal perforation. However, the etiology of IMP remains unclear. We reviewed the available literature and found that the largest number of IMP cases was reported in Japan, followed by China. Long-term Chinese herbal medicine intake may be implicated in the etiology of IMP. Therefore, further studies are needed to explore the specific risk factors and etiology of IMP to identify high-risk groups and reduce the probability of developing IMP.